2017
DOI: 10.1007/s11547-017-0757-3
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium retention in the body: what we know and what we can do

Abstract: Gadolinium-based contrast agents (GBCA), widely used in Magnetic Resonance Imaging (MRI) for almost 30 years, were recently shown to be deposited in the brain and to induce persistent T1 shortening in deep gray matter structures in subjects with normal renal function. The aim of the present study is to summarize the evidence derived from the rapidly growing scientific literature on Gadolinium retention in the brain and in the rest of the body. To this end, the original articles that described imaging and patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 97 publications
1
51
0
Order By: Relevance
“…Nevertheless, a significant renal impairment is present in FD patients (Pisani et al, 2014). This clinical finding, coupled to the recent concerns raised about a possible gadolinium deposition in the brain of patients undergoing multiple contrast MRI exams (Tedeschi et al, 2017), indirectly support the use of feasible and easy-to-identify neuroradiological signs, such as the combined callosal-infratentorial evaluation, to differentiate FD from MS.…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, a significant renal impairment is present in FD patients (Pisani et al, 2014). This clinical finding, coupled to the recent concerns raised about a possible gadolinium deposition in the brain of patients undergoing multiple contrast MRI exams (Tedeschi et al, 2017), indirectly support the use of feasible and easy-to-identify neuroradiological signs, such as the combined callosal-infratentorial evaluation, to differentiate FD from MS.…”
Section: Discussionmentioning
confidence: 94%
“…[10][11][12][13][14][15] In particular, Gd element is found in human bones and plays a key role in bone tissue growth and regeneration. [19][20][21][22] In this study, we successfully fabricated Gd-BG scaffolds with hierarchical pores and bioactive Gd element for effective bone defect healing.…”
Section: Discussionmentioning
confidence: 99%
“…18 Many studies have shown a considerably higher level of Gd deposition in bone tissue, indicating that bone might be a preferential site of Gd deposition. [19][20][21][22] Thus, Gd-containing biomaterials have attracted considerable interest worldwide. 23,24 The in vitro studies have shown that Gd could promote the proliferation of various kinds of cells.…”
Section: Introductionmentioning
confidence: 99%
“…Gaussian noise was added in k-space. k-Space SNR was defined as = ( ) [4] where rms(I) represents was the root-mean-square intensity of the noiseless k-space measurements and  is the standard deviation of the added noise signal. Three noise conditions were simulated, i) no noise, ii) moderate noise (SNRk = 185.7), and iii) high noise (SNRk = 92.8).…”
Section: Simulationsmentioning
confidence: 99%
“…Gadolinium-based contrast agents are unsuitable for patients with renal dysfunction because they can trigger nephrogenic systemic fibrosis (2), and have also been shown to be retained in the brain (3). Although the long-term health implications of gadolinium retention are still unknown (4,5), minimizing the use of gadolinium based contrast agents is recommended for clinical applications and research use.…”
Section: Introductionmentioning
confidence: 99%